2021
DOI: 10.1021/acs.jafc.1c02279
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy for the Recognition of Adulterant Vegetable Oils in Essential Oils Commonly Used in Food Industries by Applying 13C NMR Spectroscopy

Abstract: Essential oils (EOs) are valuable products commonly employed in the food industry and intensively studied as biopreservatives for the extension of food shelf-life. Unfortunately, EOs might be counterfeit to increase industrial profits. Among the possible adulterants, vegetable oils (VOs) must be considered for their characteristics and low costs. We aimed to apply nuclear magnetic resonance (NMR) spectroscopy for the detection and identification of VOs in mixtures with EOs. This innovative strategy is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…In our previous work, an efficient method for the detection and identification of vegetable oils in mixtures with EOs was developed and validated. The recognizing method was based on the creation of specific chemical fingerprints for the most common vegetable oils, which can be employed as adulterants [ 21 ]. Here, the actual quantification of the adulterant content was attempted by employing qNMR both on proton and carbon spectra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, an efficient method for the detection and identification of vegetable oils in mixtures with EOs was developed and validated. The recognizing method was based on the creation of specific chemical fingerprints for the most common vegetable oils, which can be employed as adulterants [ 21 ]. Here, the actual quantification of the adulterant content was attempted by employing qNMR both on proton and carbon spectra.…”
Section: Resultsmentioning
confidence: 99%
“…All the experiments were performed at 300 K and non-spinning. The assignments of vegetable oils' signals were carried out using standard compounds and by comparison of 1 H-NMR and 13 C-NMR spectra with literature data in our previous work [21].…”
Section: Nmr Spectroscopy and Spectra Acquisition Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods, however, generally require the use of multivariate statistical elaborations (principal component analysis and independent component analysis) or the building up of artificial neural networks, thus implying a further step of data processing. Very recently, Truzzi et al reported a method based on NMR spectroscopy without a further statistical step not only able to detect the presence of an adulteration with vegetable oils but, also, to identify the added adulterant through its 13 C-NMR fingerprint [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise identification of vegetable oil is often difficult due to the signal overlap of similar molecules [ 11 ]. Very recently, Truzzi et al introduced a new method based on 13 C-NMR spectroscopy to recognise adulterant vegetable oils in EO; the method does not require additional data elaboration with a multivariate analysis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%